On some topological properties of a new type difference sequence spaces - Karakas, Abdulkadir; Altin, Yavuz; Et, Mikail (Amer Inst Physics, 2015)
We define the sequence spaces l(infinity) (Delta(p)), c (Delta(p)) and c(0) (Delta(p)), give some topological properties and inclusion relations of these sequence spaces.
International Conference on Advancements in Mathematical Sciences (AMS) -- NOV 05-07, 2015 -- Antalya, TURKEY
Keywords: Sequence spaces; Difference sequence spaces